Seismic soil structure interaction of navigation locks - Maltidis, Georgios (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2017)
This work handles the seismic soil- and water structure interaction of navigation locks in the field of elastodynamics. The investigation is based on numerical analysis with the finite element method. The findings extend the results of available theories and studies and allow for a more precise analysis and design of such structures. Suggestions about the numerical analysis of such problems are also presented. The results can be used also for quay and retaining walls.